Experiences of (Mis)Recognition in Language Classes and Asylum Seekers’ Camp: An Account - Oshodi, Darasimi Powei (INSTED: Interdisciplinary Studies in Education & Society, 2022)
Encounters between immigrants and members of the host society throw up discourses on topics such as integration, assimilation, and discrimination. Some scholars have argued that the social class or educational level of migrants can play a significant role in their experience of living in the receiving society (Morrice et al., 2017; Portes, 2010). Therefore, the objective of this paper is to explore how a black asylum seeker perceived Italians from his experiences in language classes and an asylum seekers’ camp. I tried to provide my understanding of why our experiences might not be similar. This study adopted a narrative method with an interpretative approach, in which narratives gathered from interviews were systematically analysed in order to arrive at an understanding (Bochner & Herrmann, 2020). Drawing on Axel Honneth’s theory of recognition (Honneth, 1995), the study found experiences of recognition and disrespect in the participant’s story, with the experiences of misrecognition seeming to shape his perception about Italians. Glimpses of recognition included being seen and valued by teachers and camp operators as someone with the potential to be a successful student while clues of misrecognition included being disrespected by teachers and camp operators, one the one hand, and a feeling of being cheated or denied justice because he was black, on the other hand. This paper concludes that the participant perceived Italians as employing othering as a strategy to feel united and that a black person was not afforded the same rights to seek redress for the violation of their rights.